The impact of analytical cognitive style on business model innovation in new ventures: The moderating role of self-efficacy and environmental uncertainty - Li Hui; Zhang Xuebing (PLoS ONE, 2025)
In the context of digital-intelligent transformation, the deep integration of data elements has reshaped the cognitive boundaries of entrepreneurial decision-making. New ventures that leverage rational, data-driven analysis to guide strategic choices can transcend the bounded rationality of traditional experiential decision-making, thereby enhancing operational efficiency, market competitiveness, and long-term sustainability. Drawing on a social cognitive perspective, this study empirically examines survey data from 138 start-up firms to investigate the impact of analytical cognitive style on business model innovation in new ventures. Results indicate that analytical cognitive style is positively associated with both efficiency-oriented and novelty-oriented types of BMI. Moreover, entrepreneurial self-efficacy positively moderates the relationship between analytical cognitive style and efficiency-oriented BMI, while negatively moderating the relationship between analytical cognitive style and novelty-oriented BMI. Additionally, environmental uncertainty negatively moderates the link between analytical cognitive style and novelty-oriented BMI. These findings provide meaningful theoretical insights into the cognitive foundations of BMI and offer practical guidance for entrepreneurs seeking to innovate under conditions of uncertainty.